1988
DOI: 10.1515/botm.1988.31.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Agar Production and Quality from Gracilaria sp. Strain G —16: Effects of Environmental Factors

Abstract: A strain of Gracilaria sp., G-16, which produces an agar with high gel strength was grown under controlled culture conditions at 3 different temperatures, 2 light quantum fluxes, 2 salinities, and under N enrichment and starvation. Best productivity occurred at 24 °C, followed by 32 °C, then 15°C. Higher light quantum fluxes and nitrogen enrichment also contributed to greater productivities. Salinity changes of 17%o versus 33%o showed minimal effect on productivity. Slight salinity effects occurred when other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
5

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 15 publications
(22 reference statements)
5
46
1
5
Order By: Relevance
“…Furthermore, Hoyle (1978) found that low agar yields in the winter were associated with higher total thallus nitrogen content in two Gracilaria species. Other studies supporting the observations are those of DeBoer (1979); Lahaye & Yaphe (1988); Bird (1988) and Oyieke (1993).…”
Section: Seasonal Variation In Agar Yieldmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, Hoyle (1978) found that low agar yields in the winter were associated with higher total thallus nitrogen content in two Gracilaria species. Other studies supporting the observations are those of DeBoer (1979); Lahaye & Yaphe (1988); Bird (1988) and Oyieke (1993).…”
Section: Seasonal Variation In Agar Yieldmentioning
confidence: 52%
“…Other factors which influence agar quality include nutrient status of the media in which algae grow (Bird, 1988;Chiles et al, 1989), age (Lignell & Pedersén, 1989) and reproductive status of the plants (Givernaud et al, 1999), molecular weight of the polymer (McKinnon et al, 1969), concentration of cations such as K + (McKinnon, 1973), methoxyl content (Arnott et al, 1974a), pyruvic acid (Arnott et al, 1974b), the concentration of alkali for seaweed treatment prior to extraction.…”
Section: Seasonal Variation In Agar Qualitymentioning
confidence: 99%
“…In this study, G. verrucosa strain G-16 was grown under controlled culture conditions at two different salinities, two light quantum fluxes, three temperatures and under nitrogen enriched or limited conditions. Subsequent analyses revealed that the most marked differences in agar properties were those between the nitrogen enriched and deficient cultures grown at 32 C and 33% (Bird, 1988;Bird et al, in press). Agar from the nitrogen enriched culture had a higher measurable gel strength (1083 g cm-2) and a lower gelling temperature (42 °C ) relative to agar obtained from nitrogen limited conditions (gel strength of 525 g cm-2, gelling temperature of 47 °C ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the basis of seasonal variations remains unclear, culture studies indicate that nutritional status (Bird et al, 1981;Craigie et al, 1984) plays a significant role. Culture studies with Gracilaria verrucosa Papenfuss strain G-16 also indicate that nitrogen availability, temperature, and salinity significantly affect the physical properties of agar gels (Bird, 1988;Daugherty & Bird, in press).…”
Section: Introductionmentioning
confidence: 99%
“…The three species with the lowest agar yields were collected during July, when temperatures can exceed 30 0 C. Gracilaria caudata was collected in December, when temperatures are much cooler. Bird (1988) (Table 5), but they still are low when compared with commercial agarophytes (Bird & Hinson, 1992). Previous comparisons of genome organization and complexity data with information for gel quality suggested a possible correlation between genome profiles and synthesis of commercial-grade agars in species of the Gracilariales (Dutcher et al, 1990;Kapraun et al, 1993b).…”
Section: Agar Characterizationmentioning
confidence: 97%